CREATION OF SPECIAL EQUIPMENT FOR PRODUCTION OF LARGE BARS UNDER COLD-BOX-AMIN-PROCESS - A. P. Melnikov; D. M. Kukuj; A. V. Cherapovich (Литьë и металлургия)
А tow of modem bar equipment for production of big bars under Cold-box-amin-process is developed as a result of carried out investigations in UP “Institute BelNIIlit